The risk of sanctions following visits by monitoring bodies; a study conducted in Albania and Honduras - Brasholt, Marie; van den Bergh, Brenda; Bllaca, Erinda; Mejía, Alba; Larsen, Marie My Warborg; Levinsen, Anne Katrine Graudal; Modvig, Jens Simon (Torture Journal, 2020)
Introduction: Independent monitoring of places of detention is considered an effective way of preventing torture, but some reports have shown that detainees may face reprisals after engaging with monitors.This pilot study aims to further investigate the nature and the extent of such reprisals. Methods: A cross-sectional survey among male prisoners in 4 prisons in Albania and 4 in Honduras was carried out using an interviewer-administered, structured questionnaire and collecting additional narrative comments. Strict ethical guidelines were followed, and follow-up visits took place to detect any sanctions following participation in the study. Results: 170 detainees were invited to participate of whom 164 accepted. Most were aware of monitoring visits and found them helpful. More than one-third reported that au- thorities had made special arrangements like cleaning and painting prior to the monitoring visits, and 34% of participants in Albania and 12% in Honduras had felt pressured to act in a specific way towards the monitors. One- fifth had experienced sanctions after the last monitoring visit, most often threats and humiliations. During the follow-up visits, the interviewees reported no incidents following their participation in the study. Discussion: This pilot study has shown that it is possible to collect information about detainees’ experience with monitoring visits through interviews while they are still detained. The fact that reprisals are reported prior to and following monitoring visits points to the need of improving monitoring methodology to further lower the risk. Further research is needed to better understand the dynamics of the sanctions taking place with the aim of reaching a deeper understanding of potential preventive measures.